HPLC analysis of vitamin B6 in foods - Ollilainen, Veli-Matti (Agricultural Research Centre of Finland, 1999)
B 6 -vitamiini (pyridoksiini) on vesiliukoinen vitamiini, joka esiintyy erilaisissa kemiallisissa muodoissa biologisissa materiaaleissa kuten eläinkudoksissa, kasvisolukoissa ja niitä sisältävissä elintarvikkeissa. Elimistössä B 6 -vitamiini edesauttaa monia biokemiallisia reaktioita mm. valkuaisaineiden ja glykogeenin aineenvaihdunnassa. Perinteisen vitamiinivaikutuksen lisäksi pyridoksiini saattaa liittyä mm. altistumiseen sydän- ja verisuonitaudeille. Tieteellistä näyttöä näistä uusista yhteyksistä ei kuitenkaan vielä ole saatu. Perinteisesti B 6 -vitamiini on määritetty elintarvikkeista mikrobiologisesti, jolloin pyridoksiini on vapautettu ns. sidotuista muodoista. Tässä työssä selvitettiin nestekromatografian (HPLC:n) soveltuvuutta B 6 -vitamiinin vapaiden ja sidottujen muotojen määrittämiseen elintarvikkeista. Kehitetyn menetelmän luotettavuus varmistettiin mm. Euroopan unionin järjestämissä laboratorioiden välisissä vertailututkimuksissa. Menetelmällä määritettiin 50 elintarvikenimikkeen eri B 6 -vitamiinimuotojen pitoisuudet. Runsaasti pyridoksiinia tai sen johdannaisia sisälsivät mm. liha ja sisäelimet (maksa ja munuaiset), kananmunan keltuainen ja hasselpähkinä. Kasviperäisten elintarvikkeiden B 6 -vitamiini koostui suurelta osin sidotuista glykosyloiduista vitamiinimuodoista. Niiden hyväksikäytettävyydestä elimistössä on varsin ristiriitaisia tietoja. Työssä saadut elintarvikkeiden B 6 -vitamiinitulokset liitetään Kansanterveyslaitoksen elintarvikkeiden koostumustietopankkiin ja niitä hyödynnetään mm. ravitsemussuunnittelussa. Työ osoitti olevan tarpeellista yhdenmukaistaa käytettäviä määritysmenetelmiä, jotta eri laboratorioissa saadut tulokset olisivat paremmin vertailukelpoisia. Tätä menetelmien yhtenäistämistä jatketaan mm. Euroopan Standardoimisliiton (CEN) työryhmissä.

The objective of this work was to evaluate the methods for determination of vitamin B6 in foods. To achieve this, the literature review focused on sample treatment and liquid chromatographic analysis of vitamin B6 related compounds. In the experimental part, the chosen sample pretreatment and the high-performance liquid chromatographic (HPLC) method were validated, and used to produce vitamin B6 data on various food items commonly consumed in Finland. The main emphasis of the sample treatment was on the extraction efficiency and the maintenance of the original concentration profile of the vitamers. Several acid extraction procedures were tested for this purpose. Perchloric acid was chosen as the extraction agent. Routine food analysis was then performed using dilute ice-cold perchloric acid extraction followed by an internally standardized ion-paired reversed-phase liquid chromatography. Food samples were hydrolyzed with takadiastase and alkaline phosphatase enzymes, phosphorylated and glycosylated vitamers were quantitated before and after the enzymatic digestion. This procedure enabled the extraction of vitamin B6 compounds in their intact forms, and the measurement of free, phosphorylated and glycosylated forms. The maintenance of the concentration profile of the vitamers was verified by using 14C -labeled pyridoxal 5'-phosphate in the examination of the extraction procedure. The extraction efficiency and laboratory performance were confirmed by interlaboratory studies. Up-to-date data on vitamin B6 content of about fifty common food items was produced. The data includes the results from meat and poultry, fish and fish product, dairy product, cereal and vegetable, and ready-to-eat food samples. Free and phosphorylated vitamin B6 compounds were measured in all food groups, and the glycosylated vitamer fraction was analyzed in all plant-derived foods. The results obtained in this work showed that vitamin B6 content of nearly all foods of plant origin was mainly comprised of glycosidically bound pyridoxine derivatives. These bound analytes are normally not taken into account in traditional analytical methods, and food composition tables lack the data of glycosylated pyridoxine. The role of the glycosylated pyridoxines need to be clarified in terms of their analytical and physiological nature. If, as it is currently assumed, the availability of the bound forms is limited for humans, the role of vegetables, cereals and other foods of plant origin as a source of vitamin B6, as well as the analytical methods should be reassessed.
Keywords: Re; elintarvike; B6-vitamiini; pyridoksiini; HPLC; nestekromatografia; analyysimenetelmät; food; vitamin B complex; pyridoxine; pyridoxal; pyridoxamine; HPLC; liquid chromatography; analytical methods